Chicken soup for the soul like mother like daughter : stories about the special bond between mother and daughters - Canfield, Jack 1944-.; Hansen, Mark Victor; Newmark, Amy. (Cos Cob, Conn. Chicken Soup for the Soul Pub., 2012)
A collection of 101 true personal stories by mothers and daughters of all ages about the magical relationship between mothers and daughters, with stories ranging from funny to inspirational to heartwarming.
Php 347.00
Donated: Gprriceta-Rojo Family 05.21.20
Keywords: Mothers and daughters -- Conduct of life -- Literary collections; Mothers -- Conduct of life -- Literary collections; Daughters -- Conduct of life -- Literary collections